Long Noncoding RNA 00473 Is Involved in Preeclampsia by LSD1 Binding-Regulated TFPI2 Transcription in Trophoblast Cells - Dan Wu; Yetao Xu; Yanfen Zou; Qing Zuo; Shiyun Huang; Sailan Wang; Xiyi Lu; Xuezhi He; Jing Wang; Tianjun Wang; Lizhou Sun (Elsevier, 2018)
Preeclampsia (PE) is a syndrome manifested by high blood pressure that could develop in the latter half of pregnancy; however, the underlying mechanisms are not understood. Recent evidence points to the function of noncoding RNAs (ncRNAs) as novel regulators of the invasion, migration, proliferation, and apoptosis of trophoblasts involved in the development of placental vasculature. Here, we investigated the role of long intergenic ncRNA 00473 (linc00473) in PE and the associated molecular mechanisms. The expression of linc00473 was downregulated in the placenta of patients with severe PE as revealed by qRT-PCR analysis. In vitro, linc00473 knockdown in trophoblast cell lines HTR-8/SVneo, JAR, and JEG3 significantly inhibited cell proliferation and promoted apoptosis, whereas linc00473 overexpression stimulated trophoblast proliferation. The mechanistic insights were provided by RNA-seq and qRT-PCR, which revealed that linc00473 could regulate the transcription of genes relevant to cell growth, migration, and apoptosis. In particular, linc00473 inhibited the expression of tissue factor pathway inhibitor 2 (TFPI2) through binding to lysine-specific demethylase 1 (LSD1). These results indicate that linc00473 could be involved in the pathogenesis and development of PE and may be a candidate biomarker as well as therapeutic target for this disease. Keywords: preeclampsia, linc00473, LSD1, proliferation